Improving The Child's Moral Development through The Storytelling Method on Children 5ÔÇô6 Years Old - Jannah, Riyadoh; Mulyanti, Fitrah; Pasco Bayan, Rocelia (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
Early Childhood Education is an educational stage that has the goal of having fun learning for children, which is carried out in an interactive and participatory manner so that aspects of children's development can be more optimal in their development process. The purpose of this research is to find out the improvement results from the application of the storytelling method to the moral development of early childhood. This research was conducted in group B which consisted of 14 children. This study used the Kemmis and McTaggart class action research design. This study used class action research. The class success rate on increasing moral development through the storytelling method has reached 75%, so that research has achieved a high and satisfying success rate. Based on the results of these observations, we can conclude that the storytelling method is very effective if applied in learning to improve children's moral development. So to further ensure the moral development of the child, a storytelling method that is more interesting, interactive, and liked by children is needed.